Aphids (Hemiptera: Aphididae) on alfalfa in Serbia: seasonal dynamics and pest status: Seasonal dynamics of alfalfa aphids - Jovičić, Ivana; Radonjić, Anđa; Petrović-Obradović, Olivera (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
Alfalfa (Medicago sativa) is the most important forage legume and one of the most widely grown crops in Serbia. Aphids (Hemiptera: Aphididae) are one of the most significant groups of pests of that crop. Three aphid species, Acyrthosiphon pisum, Aphis craccivora and Therioaphis trifolii, are considered as important pests of alfalfa in Serbia. The most abundant of them, T. trifolii, is more adapted to warmer temperatures and it is the predominant aphid species during summer months, while A. pisum is prevalent during the spring period. In warmer climates, an increasing abundance of T. trifolii and decreasing populations of A. pisum have been observed in alfalfa in Serbia. On the other hand, A. craccivora is a minor pest of alfalfa, which rarely occurs in high numbers. The present paper synthesizes the existing knowledge about these three aphid pests of alfalfa, including their morphology, biology, seasonal dynamics, pest status and effects of temperature on their development.